Gerakan Membangun Kepedulian Masyarakat Terdampak Covid-19 - Hermawansa; Imma; Fitria , Yenni; Selviani , Diah; Lutfhia , Izza (Jurnal Kewirausahaan dan Bisnis, 2021)
Based on the Community Service activities that were carried out on July 9 2021, we received a good response from the community as seen from their remarks welcoming the presence of the PKM FKIP Team of Computer Education Study Program, Dehasen University Bengkulu. The activity of distributing gifts in the form of lunches, masks and vitamin C drinks is one of the social actions carried out to show high concern and empathy for the community, especially those affected by Covid-19. Through this activity, the general public will build awareness for people affected by Covid-19. The distribution of gifts was carried out at several points other than the SASPAL base camp in Bengkulu City, which could generate a sense of empathy from other members of the public. This activity can also be implemented by other parties with a broader target. This positive activity must receive appreciation from the people or institutions that have contributed to the movement to build awareness for the community affected by Covid-19. Community Service Activities that have been organized by FKIP Lecturers in the Computer Education Study Program, Dehasen University, Bengkulu, are a form of implementing the Tri Dharma of Higher Education. Therefore, this activity is very limited to certain groups and at certain times. It is hoped that activities like this can get fuller support so that they reach more of the implementation targets. In addition, with full support from Dehasen Bengkulu University or other groups, this activity can be carried out in a sustainable manner. The Movement to Build Concern for Communities Affected by Covid-19 needs to be echoed more widely so that this movement is better known by the wider community. So that the number of community participation in carrying out this activity will increase.